Islamic Business Ethics Review of Chicken Farming Business in the Middle of Community Settlements in North Luwu Regency - Mas, Nur Amal; Karmila, Karmila (JURNAL EKONOMI SYARIAH, 2023)
Introduction to the Problem: The presence of a chicken farm in the middle of the North Luwu District community settlement has positive and negative impacts which are studied based on the perspective of Islamic business ethics.Purpose/Objective Study: This study aims to analyze the review of Islamic business ethics towards chicken farming in Katulungan Village and to find out the impact arising from chicken farming activities in the middle of the Ketulungan Village community settlement.Design/Methodology/Approach: This research is a qualitative descriptive study. Data was obtained through observation, interviews, and documentation. Furthermore, the data obtained were analyzed using data collection techniques, data reduction, data presentation as well as conclusions and data verification.Findings: The results of the study explain that chicken farms that exist in the midst of community settlements are reviewed based on aspects of Islamic business ethics in the form of the principles of unity, balance/fairness, free will/effort, accountability, and truth, as well as virtue and honesty. Based on these aspects, there are livestock activities that are appropriate and not in accordance with the principles of Islamic business ethics. In addition, the presence of these farms has more negative impacts than positive impacts on the surrounding community.Paper Type: Research Article